Stage‐dependent teratogenic and lethal effects exerted by ultraviolet B radiation on Rhinella (Bufo ) arenarum embryos - Castañaga, Luis Alfredo (2009)
The adverse effects of ultraviolet B radiation from 547.2 to 30,096 J/m2 on morphogenesis, cell differentiation, and lethality of amphibian embryos at six developmental stages were evaluated from 24 up to 168 h postexposure. The ultraviolet B radiation lethal dose 10, 50, and 90 values were obtained for all developmental stages evaluated. The lethal dose 50 values, considered as the dose causing lethality in the 50% of the organisms exposed, in J/m2 at 168 h postexposure, ranged from 2,307 to 18,930; gill circulation and blastula were the most susceptible and resistant stages, respectively. Ultraviolet B radiation caused malformations in all developmental stages but was significantly more teratogenic at the gill circulation and complete operculum stages. Moreover, at the gill circulation stage, even the lowest dose (547.2 J/m2) resulted in malformations to 100% of embryos. The most common malformations were persistent yolk plug, bifid spine, reduced body size, delayed development, asymmetry, microcephaly and anencephaly, tail and body flexures toward the irradiated side, agenesia or partial gill development, abnormal pigment distribution, and hypermotility. The stage-dependent susceptibility to ultraviolet B radiation during amphibian embryogenesis could be explained in the framework of evoecotoxicology, considering ontogenic features as biomarkers of environmental signatures of living forms ancestors during the evolutionary process. The stage-dependent susceptibility to ultraviolet B radiation on Rhinella (Bufo) arenarum embryos for both lethal and teratogenic effects could contribute to a better understanding of the role of the increased ultraviolet B radiation on worldwide amphibian populations decline.